Technological resources and reading comprehension skills among superior basic education students at a public institution in Loja, academic year 2023 – 2024 - Yaguana Ramírez, Angie Michelle (2024)
Reading comprehension implies an intentional, committed and dynamic process within the acquisition of the English language, which takes place before, during and after a text, therefore, this Curricular Integration Work deals with the use of technological resources and reading comprehension. Among these resources are digital flashcards, Quizizz, and mind maps in Canva, in order to explore their benefits to improve the aspects of vocabulary, background knowledge and summarizing. The objective of this study is: To improve reading comprehension by the use of technological resources among superior basic education students at a public institution in Loja. In relation to this objective, two sub-objectives were established, the first related to identifying the effectiveness of the use of technological resources to improve reading comprehension and the second focused on describing the perception of students regarding the application of technological resources to improve reading comprehension skills. The research approach used was the mixed method based on action research in which the researcher used quantitative and qualitative methods to achieve a better understanding of the problem. In addition, field notes and a survey were used to collect qualitative data related to the student's perceptions, which were interpreted through descriptive statistics and examined with thematic analysis. The results obtained from the implementation of technological resources reveal a positive and significant impact on the improvement of reading comprehension among students. Finally, through the use of these resources, the researcher concluded that students were able to comprehend complex texts facilitating a deep understanding of reading comprehension. In this way, it allowed students to become more independent and active readers, using the technological resources to navigate through the texts with greater dexterity. Key words: Comprehension, skills, active reading